2020
DOI: 10.1111/eci.13446
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis on the diagnostic performance of magnetic resonance imaging and transient elastography in nonalcoholic fatty liver disease

Abstract: Background Noninvasive methods have been used for the assessment of hepatic steatosis in patients with nonalcoholic fatty liver disease (NAFLD). The aim was to assess the efficacy and accuracy of both magnetic resonance imaging(MRI) and transient elastography(TE) for the evaluation of hepatic steatosis. Materials and Methods The PubMed, Cochrane Library, Embase, MEDLINE and Web of Science databases were searched to retrieve studies examining the accuracy of MRI‐proton density fat fraction(PDFF) and TE‐controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Moreover, the diagnosis would be wrong in only 5% and 13% of the patients with a "negative" measurement of MRI-PDFF and TE-CAP, respectively. In consistence with the previous articles in adults, this study showed that MRI-PDFF has high accuracy in detecting steatosis of NAFLD (36).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover, the diagnosis would be wrong in only 5% and 13% of the patients with a "negative" measurement of MRI-PDFF and TE-CAP, respectively. In consistence with the previous articles in adults, this study showed that MRI-PDFF has high accuracy in detecting steatosis of NAFLD (36).…”
Section: Discussionsupporting
confidence: 88%
“…MRI-PDFF has been shown to be a highly precise, accurate, and reproducible non-invasive method for the quantification of liver fat content (33,34). Furthermore, it has been proven to correlate well with MRS (r 2 = 0.99, p < 0.001) (37) and liver biopsy (36). In addition, MRI-PDFF has been demonstrated to be superior to ultrasound, CT, and TE-CAP in the quantification of liver fat content (13,37).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, this meta-analysis compared CAP with MRI and concluded that MRI was significantly more accurate to diagnose steatosis. 96 A large individual patient data meta-analysis evaluated the use of the XL probe, which is predominantly used in NAFLD patients due to the link with obesity, and concluded that CAP can help in diagnosing steatosis, but cannot adequately grade steatosis. 97 A Canadian meta-analysis compared all meta-analyses and proposed the following cut-off values: 248 dB/m, 268 dB/m, and 280 dB/m, corrected by BMI and presence of co-morbidities, to respectively diagnose S ⩾ 1, S ⩾ 2, and S3.…”
Section: Diagnostic Modalities Of Nafld and Their Application In T1d Cohortsmentioning
confidence: 99%